Komunikasi Organisasi Di Pesantren Al-Bi’tsatil Islamiyah Panyabungan Timur - Erawadi, Erawadi (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
mic Boarding School. In detail, the formulation of this research consists of: (a) how is the communication between the leadership of the pesantren and the teachers of the Al-Bi'tsatil Islamiyah Islamic boarding school, (b) how is the communication between the teachers and the leadership of the Al-Bi'tsatil Islamiyah Islamic boarding school, and (c) how is the communication between teachers and teachers at the Al-Bi'tsatil Islamiyah Islamic Boarding School. To obtain the necessary data, interview, observation and document studies were used. Meanwhile, to analyze the data used data reduction procedures, data presentation, and drawing conclusions/data verification. Meanwhile, to ensure the validity of the data, triangulation was carried out between methods which included cross-checking between methods, namely the interview, observation and documentation methods in addition, triangulation of data sources, namely data from the heads of Islamic boarding schools and madrasas checked for correctness with data from the leadership staff, data from teachers/ustaz , and data from education personnel. There are three findings in this study, namely: Communication between pesantren leaders and teachers is carried out through deliberation activities in formal pesantren leadership meetings, and recitation/muzakkarah events at Islamic boarding schools, and at commemoration ceremonies for Islamic holidays; the birthday of the prophet Muhammad SAW, the isra 'mi'raj event, and the Hijriyah new year. Communication between teachers and leaders of pesantren and madrasas (communication from the bottom up) is carried out in conveying ideas, complaints, and reports on the implementation of teaching assignments, additional tasks, and social tasks that require solving problems faced 3. Communication between teachers and teachers (horizontally) is carried out in task coordination, activity committee meetings, and evaluations in the context of planning, evaluating, implementing tasks, and making learning guides and fostering students.